2017
DOI: 10.15381/rpb.v24i3.13905
|View full text |Cite
|
Sign up to set email alerts
|

Mutaciones en la región determinante de resistencia a quinolonas (QRDR) del gen gyrA de Neisseria gonorrhoeae presente en muestras clínicas de hombres que tienen sexo con hombres

Abstract: LSP realizó los procedimientos de laboratorio y JAC realizó el análisis del secuenciamiento. LSP redactó el manuscrito y JAC contribuyó a éste y lo revisó.Los autores no incurren en conflictos de intereses. Presentado:04/06/2017 Aceptado:03/08/2017 Publicado online: 28/10/2017 ResumenNeisseria gonorrhoeae resistente a quinolonas (QRNG) es un problema muy importante en salud pública por su rápido desarrollo de resistencia a quinolonas, por lo que la OMS recomienda reforzar la vigilancia de resistencia antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…After removing duplicates, the literature searches identified 1290 articles to be screened using title and abstract, of which 279 were retrieved for full-text assessment. Of these, 115 epidemiological studies [ 24 – 138 ] (three of which also reported data on antimicrobial resistance) [ 47 , 122 , 138 ] and one economic study [ 139 ] were eligible for inclusion in the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, the literature searches identified 1290 articles to be screened using title and abstract, of which 279 were retrieved for full-text assessment. Of these, 115 epidemiological studies [ 24 – 138 ] (three of which also reported data on antimicrobial resistance) [ 47 , 122 , 138 ] and one economic study [ 139 ] were eligible for inclusion in the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies provided data on AMR in the following countries: Argentina ( n = 10) 29 , 45 , 48 , 52–54 , 63 , 66 , 67 , 70 during 1993 and between 2000 and 2017; Brazil ( n = 9) 42 , 44 , 46 , 47 , 50 , 55 , 57 , 58 , 65 in 2003 to 2016; Colombia ( n = 2) 43 , 61 in 2009 to 2018; Peru ( n = 6) 56 , 59 , 60 , 62 , 68 , 69 in 2012 to 2017; Uruguay ( n = 1) 41 in 2010 and 2011; and Venezuela ( n = 1) 51 during 2008. There were also two studies reporting on AMR in various LAC countries from the WHO-GASP-LAC, one of which 49 reported resistance between 1990 and 2011 in 23 LAC countries, and the other reported data from 2010 and 2011 in seven LAC countries.…”
Section: Resultsmentioning
confidence: 99%
“… 60 The remaining four studies analysed only ciprofloxacin. 62 , 65 , 68 , 69 The antibiotics included in studies evaluating several antibiotics were ciprofloxacin ( n = 26), penicillin ( n = 25), tetracycline ( n = 24), azithromycin ( n = 21), ceftriaxone ( n = 19), cefixime ( n = 8), spectinomycin ( n = 7), ceftriaxone/cefixime combined ( n = 5), gentamicin ( n = 3), erythromycin ( n = 1), chloramphenicol ( n = 1), cefoxitin ( n = 1) and ofloxacin ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation